2022
DOI: 10.3389/fimmu.2022.948601
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models based on immunological genes to predict the response to neoadjuvant therapy in breast cancer patients

Abstract: Breast cancer (BC) is the most common malignancy worldwide and neoadjuvant therapy (NAT) plays an important role in the treatment of patients with early BC. However, only a subset of BC patients can achieve pathological complete response (pCR) and benefit from NAT. It is therefore necessary to predict the responses to NAT. Although many models to predict the response to NAT based on gene expression determined by the microarray platform have been proposed, their applications in clinical practice are limited due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…In particular, we identified an 87 gene signature that predicted better OS, RFS, and DMFS in basal and HER2+ breast cancer. Our data are consistent with recently published reports [14,15] and with our recently published work on single-cell analysis of TNBC in the context of TNBC response to NAC [7]. This interesting observation raises a key question about whether TNBC tumors with heavy immune infiltration represent different molecular subtype with different sensitivity to NAC compared to tumors lacking immune infiltration, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, we identified an 87 gene signature that predicted better OS, RFS, and DMFS in basal and HER2+ breast cancer. Our data are consistent with recently published reports [14,15] and with our recently published work on single-cell analysis of TNBC in the context of TNBC response to NAC [7]. This interesting observation raises a key question about whether TNBC tumors with heavy immune infiltration represent different molecular subtype with different sensitivity to NAC compared to tumors lacking immune infiltration, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…RNA-Seq data were retrieved from the PRJNA688066 [14] (discovery) and GSE192341 [15] (validation cohort): Clinical characteristics for patients from both cohorts are shown in Table 1.…”
Section: Study Cohortsmentioning
confidence: 99%
“…This yielded, as expected, high accuracy for both PathExt genes (AUROC of 0.76) as well as DEG genes (AUROC of 0.75). However, when, we tested the performance of the aforementioned model (trained and tested using GSE41998 dataset) on an additional independent dataset GSE163882 57 and observed that PathExt identified genes’ expression discriminates responders and non-responders with high AUROC of 0.72 and AUPRC of 0.79 [ Figure 7 A] compared to DEGs, which achieved an AUROC of 0.65 and AUPRC of 0.75 [ Figure 7 B]. All the training and testing were done using only the samples classified as TNBC.…”
Section: Resultsmentioning
confidence: 99%
“…Some patients are unable to undergo surgery due to disease progression during treatment [30]. For example, clinical research revealed that Neoadjuvant chemotherapy might exacerbate postoperative complications, which led to a negative prognostic impact [31][32][33][34][35]. It is therefore essential and necessary to predict the response to NAT in order to optimize treatment planning.…”
Section: Discussionmentioning
confidence: 99%